Count transformation models. Issue 7 (4th April 2020) - Siegfried, Sandra; Hothorn, Torsten
Abstract: The effect of explanatory environmental variables on a species' distribution is often assessed using a count regression model. Poisson generalized linear models or negative binomial models are common, but the traditional approach of modelling the mean after log or square root transformation remains popular and in some cases is even advocated. We propose a novel framework of linear models for count data. Similar to the traditional approach, the new models apply a transformation to count responses; however, this transformation is estimated from the data and not defined a priori. In contrast to simple least‐squares fitting and in line with Poisson or negative binomial models, the exact discrete likelihood is optimized for parameter estimation and inference. Simple interpretation of effects in the linear predictors is possible. Count transformation models provide a new approach to regressing count data in a distribution‐free yet fully parametric fashion, obviating the need to a priori commit to a specific parametric family of distributions or to a specific transformation. The models are a generalization of discrete Weibull models for counts and are thus able to handle over‐ and underdispersion. We demonstrate empirically that the models are more flexible than Poisson or negative binomial models but still maintain interpretability of multiplicative effects. A re‐analysis of deer–vehicle collisions and the results of artificial simulation experiments provide evidence of the practical applicability of the model framework. In ecology studies, uncertainties regarding whether and how to transform count data can be resolved in the framework of count transformation models, which were designed to simultaneously estimate an appropriate transformation and the linear effects of environmental variables by maximizing the exact count log‐likelihood. The application of data‐driven transformations allows over‐ and underdispersion to be addressed in a model‐based approach. Models in this class can be compared to Poisson or negative binomial models using the in‐ or out‐of‐sample log‐likelihood. Extensions to nonlinear additive or interaction effects, correlated observations, hurdle‐type models and other more complex situations are possible. A free software implementation is available in the cotram add‐on package to the R system for statistical computing. Abstrakt: Der Effekt erklärender ökologischer Variablen auf die Verteilung einer Art wird oft durch ein Zähldatenmodell beschrieben. Häufig werden generalisierte lineare Modelle mit Poissonverteilung oder Negativ Binomialmodelle verwendet, jedoch ist der traditionelle Ansatz der Modellierung des Mittelwerts nach einer logarithmischen oder Wurzeltransformation weiterhin beliebt und wird gelegentlich sogar empfohlen. Wir schlagen in dieser Arbeit eine neue Klasse linearer Modelle für Zähldatenregression vor. Dabei werden, ähnlich zum traditionellen, Ansatz, Zähldaten transformiert; allerdings wird diese Transformation datengetrieben bestimmt und ist nicht a priori definiert. Im Gegensatz zur Anwendung eines Normalverteilungsmodells nach Transformation, und in Analogie zu Poisson‐ oder Negativ Binomialmodellen, wird die exakte diskrete Likelihood für die Parameterschätzung und Inferenz verwendet. Die geschätzten Regressionskoeffizienten in dieser neuen Modellklasse sind einer einfachen Interpretation zugänglich. Transformationsmodelle für Zähldaten ermöglichen einen neuen parametrischen, jedoch nahezu verteilungsfreien, Ansatz, welcher ohne eine a priori festgelegte Verteilung der Zielgröße und ohne datenunabhängig bestimmte Transformation derselben auskommt. Die Modelle sind als Generalisierung von diskreten Weibullmodellen für Zähldaten zu verstehen und berücksichtigen als solche auch Über‐ und Unterdispersion. Wir demonstrieren empirisch, dass die Modelle flexibler als Poisson‐ oder Negativ Binomialmodelle sind und wie Ergebnisse mittels multiplikativer Effekte interpretiert werden können. Eine Zweitanalyse von Wildunfalldaten sowie die Resultate einer Simulationsstudie illustrieren die praktische Relevanz dieses Modellierungsansatzes. Unsicherheiten, ob und wie Zähldaten in ökologischen Studien transformiert werden können oder sollten, werden im Rahmen von speziell für diese Fragestellung entwickelten Zähldatentransformationsmodellen aufgelöst. Die Schätzung einer geeigneten Transformationen erlaubt es ebenfalls, Über‐ und Unterdispersion zu modellieren. Modellvergleiche sind über die auf Trainings‐ oder Testdaten evaluierte Likelihood möglich. Erweiterungen zu nichtlinearen oder Interaktionseffekten, korrelierten Beobachtungen, Schwellenwertmodellen oder anderen komplexen Analysen können durchgeführt werden. Eine Implementation der vorgeschlagenen Methode ist im quelloffenen Zusatzpaket cotram zum R ‐System für statistisches Rechnen und Grafik verfügbar.